Peran Pemerintah Daerah Kabupaten Flores Timur dalam Penyelenggaraan Wisata Religius Semana Santa Larantuka - Zakharias Pelate Demon Muda Makin; Jacob Wadu; Theny I.B.K Pah (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This study aims to analyze the role of the Regional Government of Flores Timur Regency in the implementation of the religious tourism event of Semana Santa in Larantuka. The study is motivated by the increasing number of pilgrims, which has not been fully supported by adequate infrastructure and governance management. A descriptive qualitative approach was employed, with data collected through interviews, observation, and documentation. Informants were selected using purposive sampling and included local government officials, religious leaders, organizing committee members, community members, and pilgrims. Data were analyzed using the interactive model of Miles and Huberman, and credibility was ensured through source and technique triangulation. The findings indicate that the local government has performed its roles as motivator, facilitator, and dynamizer as proposed by Pitana and Gayatri. However, implementation remains suboptimal, particularly in equitable public outreach, provision of facilities such as accommodation and clean water, and cross-sector coordination. Community participation serves as the main supporting factor, while limited infrastructure and the absence of structured official guidelines constitute major constraints. The study recommends strengthening governance through more planned, participatory, and sustainable strategies to enhance the quality of Semana Santa as a leading religious tourism destination.